2017
DOI: 10.1002/dta.2157
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral microdialysis coupled to LC–MS/MS for the determination tramadol and its major pharmacologically active metabolite O‐desmethyltramadol in rat brain microdialysates

Abstract: A rapid and sensitive method involving liquid chromatography electrospray tandem mass spectrometry (LC-ESI-MS/MS) coupled to an intracerebral microdialysis technique was developed for the determination and pharmacokinetic investigation of tramadol and its major active metabolite O-desmethyltramadol (ODT) in rat brain. The microdialysis samples were separated on a C18 column and eluted with a mobile phase of acetonitrile-water-formic acid (50:50:0.1; v/v/v) at a flow rate of 0.3 mL/min. The ESI-MS/MS spectra we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Tramadol, ODSMT, NDSMT, and their isotopomers, tramadol-D 3 -13 C, Odesmethyltramadol-D 6 and N-desmethyltramadol-D 3 were analyzed by LC-ESI-MS/MS assay adapted from previously published methods (Verplaetse and Tytgat, 2012, Tanaka et al, 2016, Liu et al, 2017. Agilent 1260 LC system, coupled with Agilent 6430 Triple Quadrupole system (Agilent Technologies) was used.…”
Section: Lc-ms/ms Assay and Sample Preparationmentioning
confidence: 99%
“…Tramadol, ODSMT, NDSMT, and their isotopomers, tramadol-D 3 -13 C, Odesmethyltramadol-D 6 and N-desmethyltramadol-D 3 were analyzed by LC-ESI-MS/MS assay adapted from previously published methods (Verplaetse and Tytgat, 2012, Tanaka et al, 2016, Liu et al, 2017. Agilent 1260 LC system, coupled with Agilent 6430 Triple Quadrupole system (Agilent Technologies) was used.…”
Section: Lc-ms/ms Assay and Sample Preparationmentioning
confidence: 99%
“…A literature survey revealed that several methods have been reported for the determination of TRM either alone or in the presence of other co‐formulated materials. These include spectrophotometric (Abdellatef, ; Amin, Adawy, Ali, & El‐Shahatt, ; Dhumal, Bhusari, Ghante, & Jain, ; Glavanović, Glavanović, & Tomišić, ; Lakshmi, Ravisankar, Kumar, & Babu, ; Thomas & Sankar, ), spectrofluorimetric (Abdellatef, El‐Henawee, El‐Sayed, & Ayad, ; Smith, Manavalan, Kannan, & Rajendiran, ), chromatographic (Baconi, Stan, Abdul Jalil Ebrahim, Tuchila, & Balalau, ; Batool, Ahmed, & Rasheed, ; Desai, Captain, & Kamdar, ; Dhumal, Bhusari, Patra, Thareja, & Jain, ; Karunakaran, Navaneethan, & Elango, ; Kiarostami, Rouini, Mohammadian, Lavasani, & Ghazaghi, ; Ravisankar, Sridevi, & Kumari, ; Solomon, Anand, Shukla, Sivakumar, & Venkatnarayanan, ), electrochemical (Chitravathi & Munichandraiah, ; Deiminiat, Rounaghi, & Arbab‐Zavar, ; Fakhari, Sahragard, Ahmar, & Tabani, ; Ganjali, Razavi, Faridbod, Riahi, & Norouzi, ; Madrakian, Alizadeh, Bahram, & Afkhami, ) and electrophoresis (Cunha, Ribeiro, Muñoz, & Richter, ) methods in addition to the hyphenated methods where the chromatographic separations are coupled with the detection (El‐Sayed, Mohamed, Nasser, Button, & Holt, ; Haage, Kronstrand, Carlsson, Kugelberg, & Josefsson, ; Liu, Wang, Yu, Dong, & Yue, ; Tambe, Deodhar, & Prakya, ; Tanaka, Naito, Mino, & Kawakami, ; Yilmaz & Erdem, ). Thus, the aim of the present study was to develop a highly sensitive, rapid and accurate LC–MS/MS method for simultaneous quantitation of TRM and some expected co‐formulated compounds.…”
Section: Introductionmentioning
confidence: 99%